Common Spatial Pattern Variants for Feature Extraction in Multi-Class Motor Imagery BCI - Fawad Asadi; Kantham Thangthong; S. Tungjitkusolmun (My University, 2025)
Brain-Computer Interfaces (BCIs) based on Motor Imagery (MI) offer intuitive control but face challenges due to noisy electroencephalography (EEG) signals that often contain artifacts, necessitating effective feature extraction. Common Spatial Pattern (CSP) is a standard technique, yet its limitations in multi-class MI scenarios motivate various extensions. This paper investigates the classification performance, computational cost, and the crucial performance versus cost trade-off inherent in practical BCI applications of five prominent CSP variants, including standard CSP, Regularized CSP (RCSP), Filter Bank CSP (FBCSP), Sparse CSP, and Kernel CSP, when applied to multi-class MI classification. Using the PhysioNet MI dataset, we employed a consistent preprocessing pipeline (18 sensorimotor channels, filtering, epoching) and evaluated each variant by feeding extracted features into a Support Vector Machine (SVM) classifier with an RBF kernel. The evaluation revealed that standard CSP and RCSP achieved the highest peak average accuracy (∼97.8%) with near-efficient computational cost. FBCSP yielded high accuracy (∼96.7%) but incurred the highest computational cost. Sparse CSP was computationally efficient but achieved lower peak accuracy (∼95.3%), while Kernel CSP showed the lowest peak accuracy (∼92.8%) at moderate cost. The findings highlight the performance profiles and efficiency of these CSP methods for this multi-class MI task, indicating that standard CSP and RCSP offer a particularly effective combination of high accuracy and manageable computational load under the evaluated conditions.
Keywords: EEG and Brain-Computer Interfaces; Gaze Tracking and Assistive Technology; Neural Networks and Applications